Corporate Governance and Dividend Policy: Evidence from Commercial Banking Sector in Nepal - Sahadev Bhatt, Dr. Swati Jain (International Journal of Modern Agriculture, 2021)
We attempt to explain how dividend payment is influenced by corporate governance system in Nepal with a sample from the commercial banking sector by utilizing a regression model of panel data. Using board characteristic variables such as board size, board independence, regularity of board meeting, and size of audit boardas the proxies of corporate governance along with profitability, capital gearing, and bank size as control variables, we explore that except audit committee size all explanatory variables are insignificant in determining the dividend payment. The size of audit committee members is positively and significantly affects dividend payout. This finding leads us to conclude that the outcome hypothesis is partially applicable and corporate governance is not an important and influencing factor to the dividend decisions in commercial banking sectors signifying that governance practice and dividend policy are not helpful in mitigating agency conflicts. It is also concluded that banking dividend payouts are not the result of the good or poor governance mechanism. Further, among other firm-specific determinants, profitability, leverage, and bank size significantly positively affect the dividend decision.